Expectant Fathers’ Social Determinants of Health in Early Pregnancy - Neri Mini, Fernanda (Glob Pediatr Health, 2020)
This cross-sectional, descriptive study examined unmet social and economic needs and health information requests of low-income, expecting fathers who participated in the First 1000 Days program. The First 1000 Days is a systems-level intervention aiming to prevent obesity among low-income mothers and infants across 3 community health centers in Greater Boston, MA, USA. Fathers who attended their partner’s first prenatal care visit were invited to complete a program survey during early pregnancy. Among 131 fathers surveyed, 45% were white, 21% were Hispanic/Latino, 55% were foreign-born, and 69% reported an annual income under $50 000. Fathers reported elevated levels of food insecurity (18%) and 33% were unaware of someone that could provide a $50 loan; however, over 85% of fathers knew someone that could provide non-financial social support. Fathers requested information about pregnancy, birth preparation, and fatherhood. Findings support addressing fathers’ unmet needs during pregnancy and providing father-specific perinatal information.